Characteristics of Morpho-Anatomy, Chlorophyll, and Phytochemistry of Myrtaceae in the Pananjung Pangandaran Nature Reserve - Anis Syarifa Romadhon; Asep Zainal Mutaqin; Rusdi Hasan (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
The Pananjung Pangandaran Nature Reserve is an Indonesian conservation area rich in species of the Myrtaceae family. This study aims to analyze the morpho-anatomical characteristics, chlorophyll content, and phytochemical compounds of the leaves of several Myrtaceae species in the area using an exploratory approach with a mixed-methods design. The observed parameters include environmental abiotic factors, leaf morphology, stomatal anatomy, chlorophyll content, and phytochemical compounds. The data were analyzed descriptively and supported by a literature review. Five Syzygium species were successfully identified, namely S. densiflorum, S. aqueum, S. lineatum, S. antisepticum, and S. polyanthum. Elliptical leaf shapes and parasitic stomatal types were dominant. The highest stomatal density was found in S. antisepticum (326,115 stomata/mm²), while the highest chlorophyll content was in S. densiflorum (53,9 CCI). Saponins were detected in all species. Abiotic factors indicate variations in environmental conditions that influence the morpho-anatomical, chlorophyll, and phytochemical characteristics of Myrtaceae species in the region .